RECEIPT OF DISPERSIBLE POWDERS FOR CARBIDES OF METALS IV -VI GROUPS FROM IONIC FUSIONS (REVIEW) - Malyshev , Victor; Gab , Angelina; Bruskova , Diana-Maria; Nesterenko , Tatiana; Kirichenko , Alex; Volyar , Roman; Ivanyuk , Ann (Scientific Journal "Metallurgy", 2020)
The historical data of fine powders of IV B-VI B groups metals carbides obtaining are given. A perspective of the high-temperature electrochemical synthesis (HTES) method is shown, possible regimes of electrolysis are considered. It is shown that the composition of the cathode product depends on the composition of the electrolyte, the conditions (temperature, cathode current density, electrode material) of electrolysis. The present state and problems of high-temperature electrochemical synthesis of carbides are considered. Enhanceable interest to the questions of development of new effective methods of receipt of carbides of metals of IV - VI of groups is predefined by continuous expandable their use for the necessities of modern technique. The comparative analysis of existent methods of synthesis of металлообразных carbides showed that one of more perspective there is a method of high temperature electrochemical synthesis (HTES) in ionic fusions. HTES can be carried out in two modes: to "thermodynamics" and "kinetic". The thermodynamics mode takes place at near standard potentials of components [1]. After such mode composition of alloy does not depend on the closeness of current in a wide interval. For the electrodeposit of metallic alloys as a criterion is offered difference of potentials of selection of components, what less or 0,2 is evened В. Differently there is the kinetic mode and composition of alloy does not depend on the difference of standard potentials. The executed served the thermodynamics ground of LIBRA by the authors of work [4] calculation of равновесных potentials (tensions) of decomposition of Eras of different connections of metals of IV - VI At a group and carbon within the limits of temperature 900-1200 К. it is set Comparison of temperature dependences of potentials of selection, that they are near in the case of refractory metals of VI of group and carbon. At the same time it is possible electrolyzing in the thermodynamics mode. The electrochemical synthesis of carbides of metals of IV and V of groups is possible only in the kinetic mode. On the basis of thermodynamics calculations and voltampermetric researches electrolytes are systematized for the receipt of dispersible powders. Influence of acid-base properties of fusions is shown on composition of cathode foods in tungsten- molybdenum- and carboncontaining-helogenide and halogenated-oxide fusions. It is shown that at presence of in the electrolytes of molybdenum and tungsten or molybdenum and tungsten with a nickel and cobalt the receipt of dispersible powders of double carbides of molybdenum and tungsten is credible, and also three-component hard-alloy compositions